Bus ticket booking via WAP - Siti Rohana, Md Saad (2009)
Nowadays, bus is one of the top public transports that are used by people.Currently,most of the bus companies still using conventional style in selling their bus ticket where customers need to go to ticket counter to buy or book the bus ticket.Another way is by purchase or book the ticket online at the internet.Thus,the objective developing this system is to change the current system into the ticket booking system via wireless application protocol (WAP) using mobile phone.The purpose of the system is to give convenient to customer because mobile phone nowadays have lots of application and something that we take along with us where ever we go.To enable this system to work, PHP and MySQL were used as the programming language and the database.During developing this system, Rapid Application Development (RAD) methodology are chosen to make the development successful.